Inovasi Pembelajaran Pantun Berbasis Kearifan Lokal - Abdul Rahman Rahim; Wardiman Wardiman; Yuni Lestari (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
Pantun is a type of old poem that is written and usually uses a tone or song. Pantun consists of the elements of a sentence of four lines in a verse, which is based (a-b-a-b). Usually the first row and the second row are sampiran, the third and fourth rows are the contents. This research aims to test the effectiveness of an innovation of learning based on local wisdom pantun namely by using a dictionary of courses. This research is categorized into experimental research types. The method used by researchers in this study is quasi experiment with one group pretest posttest design model. The population is all students of class V sdn 331 Borongtellutahun 2020/2021. The population numbered 30 people as well as a sample of the study. This study uses tests to find out the ability to write the student guide The test is given twice, namely pre-action and post-action. The data in this study were analyzed using statistical techniques inference design analysis, simple linear regression. Based on the results of this study, it can be concluded that the results of learning to write pantun students of grade V SD Negeri 331 Borongtellu using conventional techniques is an average of 67.74 in the range of 10-100 grades with a moderate category. After being treated using rhyming dictionaries and lateral thinking, the student's learning outcomes averaged 79.33in the range of grades 10-100 with a high category. Thus the use of rhyming dictionaries and lateral thinking effective in improving the results of writing local wisdom-based pantun learning in grade V students of SD Negeri 331 Borongtellu, because the t-count /empirical value is greater than the table/theoretical t-value (14.27>1.6709).